A cost utility analysis of treating different adult spinal deformity frailty states. (October 2020) - Brown, Avery E.; Lebovic, Jordan; Alas, Haddy; Pierce, Katherine E.; Bortz, Cole A.; Ahmad, Waleed; Naessig, Sara; Hassanzadeh, Hamid; Labaran, Lawal A.; Puvanesarajah, Varun; Vasquez-Montes, Dennis; Wang, Erik; et al.
Highlights: Cost utility analysis of surgical treatment for ASD in different frailty states. F and SF patients had lower Cost/QALY compared to non-frail patients at 2 years and life expectancy. ASD surgery is a cost-effective treatment option in both NF and F/SF groups. Abstract: The aim of this study was to investigate the cost utility of treating non-frail versus frail or severely frail adult spinal deformity (ASD) patients. 79 surgical ASD patients >18 years with available frailty and ODI data at baseline and 2-years post-surgery (2Y) were included. Utility data was calculated using the ODI converted to the SF-6D. QALYs utilized a 3% discount rate to account for decline to life expectancy (LE). Costs were calculated using the PearlDiver database. ICER was compared between non-operative (non-op.) and operative (op.) NF and F/SF patients at 2Y and LE. When compared to non-operative ASD, the ICER was 447, 943.96 vs. 313, 211.01 for NF and F/SF at 2Y, and 68, 311.35 vs. 47, 764.61 for NF and F/SF at LE. Frail and severely frail patients had lower cost per QALY compared to not frail patients at 2Y and life expectancy, and had lower ICER values when compared to a non-operative cohort of ASD patients. While these results support operative correction of frail and severely frail patients, it is important to note that these patients are often at worse baseline disability, which is closely related to frailty scores, and have more opportunity to improve postoperatively. Furthermore, there may be a threshold of frailty that is not operable due to the risk of severe complications that is not captured by this analysis. While future research should investigate economic outcomes at extended follow up times, these findings support the cost effectiveness of ASD surgery at all frailty states.